Molecular identification of lactic acid bacteria isolated from tempoyak made of Malaysian Durian Musang King, Budu and Fermented Chili / Muhamad Nazmie Rahmad - Rahmad, Muhamad Nazmie (2015)
Malaysia has many traditional fermented food and every states in Malaysia have their own traditional food for example like Budu, Tempoyak and Chili Bo. Lactic acid bacteria (LAB) are an important group of industrial organism that involved in the processing of various fermented food. Previous study shown, screening and identification of lactic acid bacteria is only focus on biochemical and analytical profile index (API) test. Therefore, this study was performed to investigate the LAB isolate made from durian musang king, budu, and fermented chili using molecular identification which is PCR analysis. The sample was sequenced by 16S rONA gene and will detect the specific bacteria strain of lactic acid bacteria due to the percentage of similarities according to sequence data accumulated from the National Center of Biotechnology Information database (NCBI) Gen Bank. Based on data collected, LAB strain was detected at 1500 base pair. The sequencing result were identified the specific strain of LAB isolated according to the high similarities percentage. Comparison between PCR and API test was done showing that PCR are given more specific strain of LAB isolated. As a conclusion, there is a LAB strain isolated from dOOan made of Malaysian durian musang king, budu and chili boo Detection by PCR gives exact strain of LAB by PCR compare to API test.